Fascin is secreted in male's serum: results of a pilot study. (5th January 2018) - Porav-Hodade, Daniel; Martha, Orsolya; Balan, Daniel; Tataru, Sabin; Hutanu, Adina; Sin, Anca; Vartolomei, Mihai Dorin
Aim: Fascin is a 55 kDa globular protein with an important role in cell migration. Aim of study was to investigate serum fascin in healthy males.Materials & methods: From 1 July 2016 to 31 December 2016, we collected serum from 46 males. Serum fascin level was performed using ELISA kit from USBiological (Salem, MA, USA).Results: Median age was 64 years. Mean fascin serum level was 9.84 ng/ml, mean prostate-specific antigen (PSA) was 2.74 ng/ml and mean prostate volume was 37.64 cc. The 51–60 years group had a mean of 10.53 ng/ml, the 61–70 group a mean of 9.7 ng/ml and the 71–80 group had a mean of 9.41 ng/ml fascin serum level.Conclusion: Fascin serum level did not differ according to age in males. Lay abstract: Fascin protein was previously associated with high-grade malignancies. This study presents the determination of fascin serum levels in 46 healthy males, providing a reference number in further determinations. The patients were divided into three subgroups according to age. The study presents the mean levels of each group, in association with PSA level and the mean prostate volumes. In conclusion, the study states that fascin is secreted in healthy male controls and the levels did not differ according to age.